Psychological effects of teacher coaching training. - Rybina O. V., Vilkovskaia O. D., Naumova T. D. (Coaching and mentoring: theory and practice, 2025)
The paper presents the findings of a study on communication effectiveness indicators and teacher burnout levels before and after coaching training. Within the scope of this research, the efficacy of communication, self-confidence, level of subjective control, and degree of burnout were assessed before and after coach technology training for educators. The data revealed a decrease in emotional exhaustion and an improvement in communication efficiency. This article underscores the potential of coaching training in enhancing the effectiveness of educational processes and promoting the well-being of educators.
Keywords: педагогика; психология; инклюзия; коммуникация; psychology; уровень субъективного контроля; communication; выгорание; burnout; pedagogy; коучинг; inclusion; coaching; коуч-технология; coaching technology; locus of control